IMPLEMENTASI MODEL PEMBELAJARAN INTERAKTIF DALAM PENINGKATAN HASIL BELAJAR IPA SISWA KELAS VI SEKOLAH DASAR - Tika Muhdaleni (Fakultas Keguruan dan Ilmu Pendidikan Univesitas Dharmas Indonesia, 2021)
This research is motivated by the low learning outcomes of SDN 0014/XI Pelag Raya, the number of students who do not reach the KKM 7. There are still many students who do not concentrate in learning, lack of experience in learning and the learning process, many students who still cannot answer the teacher's questions, there are still many students playing in class. This type of research is classroom action research. The subjects of this study were students of SDN 0014/XI Pelag Raya Sungai Penuh City class VI in the first semester of the 2020/2021 academic year. The types of data used in this study include quantitative and qualitative information. Quantitative data is information collected and analyzed from student learning outcomes during the learning process. In the first cycle, the classical completeness of the students was 46%, the average score was 74.3, then the second cycle increased by 79% and the average score was 84.3%, which is 33%, from cycle I to cycle II. Thus, interactive learning models can improve processes and improve learning outcomes for students in science by changing their energy and its consequences in their daily lives.